2014
DOI: 10.1088/0004-637x/790/2/138
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismic Estimate of Helium Abundance of a Solar Analog Binary System

Abstract: 16 Cyg A and B are among the brightest stars observed by Kepler. What makes these stars more interesting is that they are solar analogs. 16 Cyg A and B exhibit solar-like oscillations. In this work we use oscillation frequencies obtained using 2.5 years of Kepler data to determine the current helium abundance of these stars. For this we use the fact that the helium ionization zone leaves a signature on the oscillation frequencies and that this signature can be calibrated to determine the helium abundance of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
137
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 69 publications
(151 citation statements)
references
References 60 publications
14
137
0
Order By: Relevance
“…The asteroseismic results are taken from Metcalfe et al (2012), their results being a collaborative effort using a number of different stellar evolution codes and detailed asteroseismic modelling approaches. The adopted age is consistent with other asteroseismic results from Gruberbauer et al (2013), ≈ 6.5 ± 0.3 Gyr, and Verma et al (2014), 6.6 ± 0.3 Gyr. Determination of the age of the system from spectroscopic parameters and isochrone fitting has produced age estimates greater than the asteroseismic results (e.g.…”
Section: Introductionsupporting
confidence: 90%
“…The asteroseismic results are taken from Metcalfe et al (2012), their results being a collaborative effort using a number of different stellar evolution codes and detailed asteroseismic modelling approaches. The adopted age is consistent with other asteroseismic results from Gruberbauer et al (2013), ≈ 6.5 ± 0.3 Gyr, and Verma et al (2014), 6.6 ± 0.3 Gyr. Determination of the age of the system from spectroscopic parameters and isochrone fitting has produced age estimates greater than the asteroseismic results (e.g.…”
Section: Introductionsupporting
confidence: 90%
“…Furthermore, it does so directly without making comparisons with theoretical predictions from models (except for interpreting the amplitude of the feature in terms of He abundance; see e.g. Verma et al 2014b), thereby making the results model-independent. In contrast, the forward modelling approach is indirect and model-dependent since it ends up implicitly comparing glitch signatures present in the observations to those obtained in theoretical models.…”
Section: Group 2: Glitch Fitting Analysismentioning
confidence: 99%
“…In fact, surface chemical composition differences between Verma et al (2014) is the same, the scatter is larger for the B component, and if microscopic diffusion is included in the stellar models, it is also clear that surface chemical composition differences will be seen since this mixing will not have the same efficiency for stars of different masses 2 . Nevertheless, it should be noted that chemical composition differences between 16CygA and 16CygB are still under some debate since their existence has been claimed by Ramírez et al (2009) andTucci Maia et al (2014) as well as by previous studies (see Deliyannis et al 2000) but could not be confirmed by Schuler et al (2011) Moreover, these values depend on the reference solar metallicity assumed in the study since the observational constraint provided is the [Fe/H] value which must be translated in a Z X value using the Sun as a reference.…”
Section: Reference Modelsmentioning
confidence: 99%
“…-Constraints: individual small frequency separations d 0,2 d 1,3 , inverted mean density (ρ) for which conservative error bars of 0.005 g/cm 3 were considered, acoustic radius (τ) for which conservative error bars of 30 s were considered, present surface metallicity (Z f /X f ) from Ramírez et al (2009), present surface helium abundance (Y f ) from Verma et al (2014) and the effective temperature from Tucci Maia et al (2014), for which we considered error bars of 30 K. In total, we had 5 free parameters for 31 constraints. In addition to these constraints, we checked the values of the luminosity L, surface gravity log g and radius R after the forward modelling to see if they were consistent with the constraints from the literature.…”
Section: Reference Modelsmentioning
confidence: 99%